"Alone in a Sea of Rib-Tips": Alvenia Fulton, Natural Health, and the Politics of Soul Food. (19th June 2019) - Weisse, Travis A
Abstract: While the intersection between alternative medicine and the natural food movement in radical white communities of the 1960s and 1970s is well known, the connection between these traditions and the simultaneous revolution in the black foodscape has not received adequate attention. This paper addresses this gap by exploring how an alternative healer and minister from the rural South, Alvenia Fulton, rose to prominence in Chicago during the 1960s and 1970s as one of the major figures in the transformation of the black diet by harnessing the star power of her celebrity clients. Fulton hybridized her apprenticeship in slave herbalism with concepts from white Protestant health food lectures into a corrective nutrition program to bring health and renewal to black communities that were struggling under the burden of structural and medical racism. When, in the 1960s, coronary heart disease peaked for black Americans, soul food became the iconic diet of the civil rights movement. To help her community while respecting their culture, Fulton struck a careful bargain to encourage more black Americans to eat raw, natural, vegetarian food by subtly reimagining the historical contents of the slave diet.